Elongator subunit 3 (ELP3) modifies ALS through tRNA modification. (3rd February 2018) - Bento-Abreu, Andre; Jager, Gunilla; Swinnen, Bart; Rué, Laura; Hendrickx, Stijn; Jones, Ashley; Staats, Kim A; Taes, Ines; Eykens, Caroline; Nonneman, Annelies; Nuyts, Rik; Timmers, Mieke; et al.
Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal degenerative motor neuron disorder of which the progression is influenced by several disease-modifying factors. Here, we investigated ELP3, a subunit of the elongator complex that modifies tRNA wobble uridines, as one of such ALS disease modifiers. ELP3 attenuated the axonopathy of a mutant SOD1, as well as of a mutant C9orf72 ALS zebrafish model. Furthermore, the expression of ELP3 in the SOD1 G93A mouse extended the survival and attenuated the denervation in this model. Depletion of ELP3 in vitro reduced the modified tRNA wobble uridine mcm 5 s 2 U and increased abundance of insoluble mutant SOD1, which was reverted by exogenous ELP3 expression. Interestingly, the expression of ELP3 in the motor cortex of ALS patients was reduced and correlated with mcm 5 s 2 U levels. Our results demonstrate that ELP3 is a modifier of ALS and suggest a link between tRNA modification and neurodegeneration.